The osteoporosis knowledge, belief and calcium intake behaviour among students in a Medical Sciences University - Chiang, Wan Ling; Mohammad Husni Ahmad Jamal, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction This study determines the association between osteoporosis knowledge, health belief and calcium intake behaviour among students in a medical sciences university. Methods This study was conducted using cross sectional design. Malaysian students, aged 18 to 40 were selected using stratified randomisation method. The osteoporosis knowledge, health belief and calcium intake behaviour of participants were obtained through a validated questionnaire. Results The response rate of the study was 93.0% (n=333). More than 80% of participants had been exposed to information related to osteoporosis knowledge and calcium-rich foods. The mean score of osteoporosis knowledge test (OKT)= 50.4±6.48, perceived susceptibility= 14.2±4.02, perceived seriousness= 20.4±4.67, perceived benefits of calcium= 23.1±3.94, perceived barriers to calcium= 14.4±3.99 and health motivation= 21.6±3.79. Only 37.8% of participants consumed adequate dairy products. There were significant correlations between OKT and perceived benefits of calcium (r=0.127, p=0.020), perceived barriers to calcium (r=-0.208, p<0.001) and health motivation (r=0.173, p=0.002). Perceived seriousness to osteoporosis, health motivation and OKT significantly predicted intake of dairy products (p<0.001). Conclusions The osteoporosis knowledge was moderate, health belief was moderate and consumption of dairy products was low. The osteoporosis knowledge and health belief were correlated but not the behaviour of dairy products consumption. Young adults had moderate osteoporosis knowledge and consumption of dairy products was low. Future educational programme should focus on osteoporosis knowledge, health belief as well as determining factors that influence behaviour of consumption of dairy products.